Desempenho do capim-tifton 85 submetido a adubação química e orgânica - Naiara Taís Alves da Silva (2015)
The tifton 85 grass offers high productivity and nutritional value. It is demanding in soil fertility and highly responsive to fertilization. The response to fertilization can be affected by the source, dose and installment of fertilizers, and the environmental conditions. Evaluations of joint application of chemical and organic fertilizers are scarce. The studies were conducted to evaluate the effect of NPK 20-00-20 and poultry litter (PL) fertilization on agronomic characteristics, use efficiency of mineral nutrients and bromatologic composition of tifton 85 grass. The highest values for height, and accumulation rate of dry matter productivity were obtained in major doses of fertilizers. The leaf/stem rate was not influenced by fertilization. The use efficiencies (UE) of the mineral nutrients reduced with high doses of PL. The largest UE of mineral nutrients were obtained in doses of 200 and 400 kg N/ha/year of NPK 20-00-20 and up to 10 t/ha/year to PL. The crude protein (CP) content increased, while the levels of NDF and ADF reduced. The protein fractions and IVDDM were not affected by fertilization. The K content increased with high doses of fertilizers.